1986
DOI: 10.1093/nar/14.11.4557
|View full text |Cite
|
Sign up to set email alerts
|

Sequence, organization and expression of late embryonic H3 and H4 histone genes from the sea urchin,Strongylocentrotus purpuralus

Abstract: A gene pair coding for histones H3 and H4 expressed during late embryonic development has been cloned from the S. purpuratus genome. The organization of these genes is similar to the divergently transcribed H3-H4 gene pairs of Lytechinus pictus. Whole genome Southern analysis indicates that most late H3 and H4 genes are organized as pairs in both sea urchin genomes. The nucleotide sequences of late and early S. purpuratus H3 and H4 genes differ in the coding regions by 17.0% and 15.7%, respectively. Although t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
27
0

Year Published

1987
1987
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…The heterogeneous family of late histone genes consists of different single-copy genes that code for distinct histone H1, H2A, and H2B variants but identical H3 and H4 proteins {Childs et al 1982;Maxson et al 1983b;Busslinger and Barberis 1985;Kaumeyer and Weinberg 1986;Knowles et al 1987;Cosson et al 1988;Lai and Childs 1988). Late histone mRNAs are absent or barely detectable in the egg, start to accumulate in the blastula embryo, but reach their maximal levels only later in embryogenesis (Maxson et al 1983b; Knowles and Childs 1984;Busslinger and Barberis 1985}.…”
mentioning
confidence: 99%
“…The heterogeneous family of late histone genes consists of different single-copy genes that code for distinct histone H1, H2A, and H2B variants but identical H3 and H4 proteins {Childs et al 1982;Maxson et al 1983b;Busslinger and Barberis 1985;Kaumeyer and Weinberg 1986;Knowles et al 1987;Cosson et al 1988;Lai and Childs 1988). Late histone mRNAs are absent or barely detectable in the egg, start to accumulate in the blastula embryo, but reach their maximal levels only later in embryogenesis (Maxson et al 1983b; Knowles and Childs 1984;Busslinger and Barberis 1985}.…”
mentioning
confidence: 99%
“…3A was used). The 30 min. The samples were placed on ice after stop buffer was added, and they were processed together for the isolation of RNA as described in the text.…”
mentioning
confidence: 99%
“…The late embryonic histone genes of Strongylocentrotus purpuratus and Lytechinus pictus are present in far fewer copies (2 to 12 members per genome, depending on the histone species) and are distributed in irregular clusters (9,30,31,33,34,40). The late mRNAs are found in low levels in the egg, but in contrast to the early mRNA species, they do not increase to their maximum levels until the mid-to late blastula stage (7,8,20,27,30,32,34,35,40,46) (42,58). In the case of late H2B mRNA synthesis, recent in vivo [3H]uridine incorporation studies demonstrated an eightfold increase in the rate of RNA accumulation between the midblastula and late blastula stages (28a).…”
mentioning
confidence: 99%
“…The core histone genes are dispersed in the genome in S to 10 irregular arrays, while the two late Hi subtypes, Hi-p and H1--y, are encoded as unique copy genes (7,28,29,32,35,41). The late histone genes are transcribed at low basal levels until the mid-blastula stage (12 to 18 h, 128 to 300 cells), after which the transcription rate increases and transcripts accumulate to a peak of about 2 x 106 molecules in the late-blastula stage embryo (21 h) (25,30).…”
mentioning
confidence: 99%